Functional performance comparison of long cane and secondary electronic travel aids for mobility enhancement. - Jin, Rui; Petoe, Matthew A; McCarthy, Chris D; Serra, Jaime R; Starkey, Scott; McGinley, Jennifer; Ayton, Lauren N (British Journal of Visual Impairment, 2026)
This study investigated the impact of secondary electronic travel aids (ETAs) on the mobility performance of individuals with profound visual impairment, specifically focusing on object detection and obstacle avoidance tasks. Seven experienced long-cane users were recruited for the study. The ETAs tested as secondary aids to the long cane included the MiniGuide, utilizing ultrasonic echo location, and the vOICe (Vision-to-Auditory Sensory Substitution Device), which translates visual information into auditory signals. Two software modes of the vOICe were examined: the standard contrast mode and a novel algorithm utilizing relative depth information. Notably, 30 min of familiarization was provided before the trials. Results indicated that while the use of the secondary ETAs led to increased awareness of the surrounding environment, it also resulted in longer processing times and more hesitations, compared with using the long cane alone. Participants demonstrated improved object detection and larger detection and safety ranges during obstacle avoidance. The study also introduced the concept of margin of stability (MoS) as a novel metric for evaluating gait stability while using ETAs. Both MiniGuide and vOICe users exhibited consistent and stable movements, suggesting that these additional aids did not negatively impact overall gait stability. The findings highlight the trade-offs between efficiency and effectiveness when using secondary mobility aids, with longer training periods potentially mitigating these issues. In addition, the study emphasizes the need for ongoing research to optimize the design and training programmes for new ETAs. Future studies may explore the impact of extended training periods on mobility performance. Overall, this research contributes to a deeper understanding of how ETAs can enhance the mobility of individuals with visual impairments while also highlighting some of the challenges associated with their use. Optimizing ETA design and training programmes is crucial for maximizing benefits for individuals with impaired vision.